IMPLEMENTASI PEMBELAJARAN SENI TEATER DENGAN METODE DEMONSTRASI DALAM MENUMBUHKAN RASA PERCAYA DIRI SISWA SEKOLAH DASAR - Afila Firda Arifa; Shofiatul Kamaliah; Nabila Hasna Utama; Roma Aristiyanto (CV. Denasya Smart Publisher, 2025)
This study aims to describe the implementation of theater art learning using the demonstration method in fostering elementary school students’ self-confidence. The background of this research stems from the low level of students’ confidence in expressing themselves in front of others, which remains a challenge in cultural arts education at the elementary level. This research employs a qualitative approach with a literature review technique, analyzing various sources such as books, scientific articles, and previous research relevant to theater art learning and the development of self-confidence. The results indicate that the demonstration method in theater learning is effective in providing direct experience to students, enhancing their courage to perform, and fostering self-confidence through observation, imitation, and practice. Furthermore, theater art learning through demonstration supports the development of students’ affective, social, and communication skills. The study recommends that cultural arts teachers in elementary schools integrate the demonstration method continuously to create active, creative, and character-oriented learning that strengthens students’ self-confidence.